Hormones - Norman, Anthony W.; Henry, Helen L. (Academic Press, 2015)
The 3rd edition of Hormones offers a comprehensive treatment of the hormones of humans all viewed from the context of current theories of their action in the framework of our current understanding their physiological actions as well as their molecular structures, and those of their receptors. This new edition of Hormones is intended to be used by advanced undergraduates and graduate students in the biological sciences. It will also provide useful background information for first year medical students as they engage in studies which are increasingly problem-based rather than discipline-focuse.